Analysis And Design Of Wireless Power Transfer System (Wireless Power Transfer) - Emil Siska Sinaga (Jurnal Mekintek : Jurnal Mekanikal, Energi, Industri, Dan Teknologi, 2020)
Wireless Power Transfer is a way of sending electrical energy through air media, so that electrical energy can be transmitted from a power source to an electrical load without using a conductor or cable. The maximum distance that can be sent by the transmitter to the receiver is 5cm with a voltage of 1.3 volts. This proves that the farther the distance between the transmitter and the receiver, the smaller the voltage and the smaller the power that can be transmitted. Likewise, if the distance between the receiver and transmitter is getting closer, the voltage and power that can be emitted will be even greater.